ESTIMATION OF THE NUMBER OF INJECTION DRUG USERS IN ST. PETERSBURG, RUSSIA - Heimer, Robert (2010)
The conjoined epidemics of HIV and injection drug abuse have progressed rapidly in many parts of the Russian Federation, including the City of St. Petersburg, which now has more cases of HIV than any other region in the country. Official estimates of the number of injection drug users (IDUs), which rely on official registration of IDUs, greatly underestimate their number. We have combined official statistics that register HIV cases and attribute risk to causes including injection drug use with data from a study that collected data from IDUs about their HIV serostatus and their history of HIV testing to estimate the number of IDUs in the city. We conclude that there are 83,118 ± 5,799 total IDUs. Since many IDUs have not been tested and even some who have been officially tested do not know their serostatus, a first step in countering the growing HIV epidemic among IDUs in St. Petersburg must be expanded access to HIV testing, prevention, and treatment that is targeted to IDUs.